Kemampuan Menganalisis pada Materi Usaha Menggunakan Model Pembelajaran Inkuiri Terstruktur Berbasis STEM - Niswatun Rohmah; Tutut Nurita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Science learning on the topic of work in junior high school still tends to focus on mathematical procedures, so students’ higher-order thinking skills, especially analyzing, have not developed optimally. This study aims to describe the implementation of learning, the improvement of students’ analytical skills, and students’ responses through the application of a structured inquiry model based on STEM. This research employed a pre-experimental design with a one group pre-test and post-test design involving 31 students of class VIII A at SMP Negeri 2 Surabaya. Data were collected through observation, tests, and questionnaires. The results showed that the implementation of learning was in the very good category (92%–100%). The average pre-test score increased from 22.05 to 77.09 in the post-test with an N-Gain of 0.7 (high category), and the paired sample t-test result showed p < 0.001. Students’ responses were also in the very good category with percentages ranging from 85% to 88%. Structured inquiry model based on STEM is effective in improving students’ analytical skills on the topic of work.